Key drivers of the spatio-temporal distribution of African elephants at Sanbona Nature and Wilderness Reserve, Little Karoo - Rifai, Aisha Salim (Stellenbosch : Stellenbosch University, 2025)
Thesis (MSc)--Stellenbosch University, 2025.